PENERAPAN MODEL KOOPERATIF WORDSQUARE UNTUK MENINGKATAN PRESTASI BELAJAR SISWA PADA PEMBELAJARAN KIMIA POKOK BAHASAN KOLOID DI KELAS XI SMKN 2 PEKANBARU - Lidiana Fitri; Nofianti '; Susilawati ' (Fakultas Keguruan dan Ilmu Pendidikan (FKIP), Universitas Riau (UNRI), 2016)
The research about application of word Square cooperative learning model has been done to improve student’s achievement in colloid matter at 11th SMKN 2 Pekanbaru. The purpose of this research was to know if the application of Word Square cooperative learning model could increase student achievement in colloid matter. Subject of this research were students at XI Kimia 1 class and XI Kimia 2 class in academic year 2011/2012. XI Kimia 1 class was randomly selected as experiment class and XI Kimia 2 class as control class. Research results revealed that application cooperative learning Word Square model was capable to improve student’s achievement in colloid matter. This research pretest-posttest design by using t-test (t arithmetic> t table; 3.49 > 1.67). The application this model capable to increase students achievement in colloid matter about 13.71%.Keywords: cooperative learning, Word Square, colloid and learning achievement